2013
DOI: 10.1021/bi301458b
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence of Fatty Acid and Drug Binding Sites on Human Serum Albumin: A Two-Dimensional Nuclear Magnetic Resonance Study

Abstract: The ability of human serum albumin (HSA) to bind fatty acids (FA) in multiple sites has been revealed by many studies. Here we detect and characterize nine individual binding sites by two-dimensional (2D) nuclear magnetic resonance (NMR) spectroscopy of 18-[(13)C]-oleic acid (OA) complexed with HSA. We characterize site-specific FA binding by addition of (i) different FA molar ratios (from 1:1 to 4:1 OA:HSA) to observe the order of filling and occupancy of binding sites; (ii) methyl-β-cyclodextrin, as a FA acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 43 publications
6
76
0
Order By: Relevance
“…The findings also support more recent NMR displacement studies which showed that FA bound to the low affinity FA6 and FA7 sites were easily displaceable [6]. Our results suggest that the more facile substrate displacement observed from sites FA6 and FA7 is a result of their greater solvent exposure (water contacts = 7.75 at FA6 and 8.43 at FA7) and fewer protein-FA hydrogen bonds and supports the findings from recent spectroscopic experiments [19].…”
Section: Hsa Binding Site Characteristics From MDsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings also support more recent NMR displacement studies which showed that FA bound to the low affinity FA6 and FA7 sites were easily displaceable [6]. Our results suggest that the more facile substrate displacement observed from sites FA6 and FA7 is a result of their greater solvent exposure (water contacts = 7.75 at FA6 and 8.43 at FA7) and fewer protein-FA hydrogen bonds and supports the findings from recent spectroscopic experiments [19].…”
Section: Hsa Binding Site Characteristics From MDsupporting
confidence: 91%
“…To date approximately 100 HSA structures have been published in the Protein Data Bank (www.rcsb.org). In addition, NMR [5,6], EPR [7] and biochemical * Corresponding author. Tel.…”
Section: Introductionmentioning
confidence: 99%
“…We found that HSA bound and released OA rapidly and with a high RU response (for example, Fig. 1E), which was expected from extensive previous studies of FA binding, including those in our lab with albumin (39,40) and FABP1 (41,42). As an additional negative control, we bound IgG to the chip surface and saw no OA binding, as expected (Fig.…”
Section: -C)supporting
confidence: 84%
“…Nine individual sites on HSA have been recently been detected by two-dimensional NMR, and several NMR peaks were correlated with crystallographic sites well characterized for long chain FA (39). Binding constants measured by two-dimensional NMR on a site-specific basis varied only by a factor of 10 between the highest and lowest affinity sites, with affinity constant (K D ) values similar to those reported by earlier studies (note:…”
Section: Fatty Acid Binding: Novel Findings From Surface Plasmonsupporting
confidence: 72%
“…The binding property (e.g., binding sites, binding affinity or strength) of these molecules to serum albumins forms an important topic in pharmacokinetics. [1][2][3][4] Several analytical methods have been developed to study the binding properties of different drugs to serum albumins, such as X-ray crystallography, 5,6 nuclear magnetic resonance (NMR), [7][8][9][10][11] and surface plasmon resonance (SPR), 12,13 etc. However, these methods are constrained by either a tedious and time-consuming analyzing process (e.g., growth of single crystal for X-ray crystallographic study), requirement of specialized and expensive equipment (SPR), or in need of costly isotope labeling (NMR) for detection.…”
Section: Introductionmentioning
confidence: 99%